Islamic Inheritance Law in Indonesia: The Influence of Hazairin's Theory of Bilateral Inheritance - Mark Cammack (Studia Islamika, 2003)
This article presents a relatively detailed account of Hazairin's theory that the Qur'an and the Traditions of the Prophet support what he refers to as a bilateral system of Islamic inheritance law. The second part of the article then examines recent developments in Islamic inheritance law in Indonesia, and argues that the law is moving, albeit slowly and tentatively, in the direction of an implementation of Hazairin's ideas.DOI: 10.15408/sdi.v10i1.639